Scenario modeling for dentistry in Malaysia: utilization, privatization, and specialization - Che Musa, Muhd Firdaus; Morgan, Jennifer; Harper, Paul; Bernabe, Eduardo; Gallagher, Jennifer E. (Wolters Kluwer, 2024)
Aim: To study to model future clinical dental workforce scenarios in Malaysia, in relation to population need–demand, to inform future change. Materials and Methods: A system dynamics (SD) model was developed in Vensim-software to model the need/ demand and supply for dental care across public–private sectors over 3 decades (2010–2040). This model included two sub-models relating to “need/demand” and “supply,” drawing on national evidence from two previous studies (student career surveys and interviews of key stakeholders nationally), together with relevant available data. This SD model provided the baseline model (S1) for Malaysia and four-distinctive-scenarios (S2–5), involving enhancing generalists–specialists across public–private sectors. An additional scenario (S6) was run to optimize workforce utilization, informed by career expectations of emerging graduates drawing on earlier scenarios (S2–5). Results: Modeling future five-scenarios highlighted the gap in dental workforce nationally across both sectors could range from a surplus of a total of 3739 dentists and 817 therapists in the baseline scenario to a total shortfall of 1249 dentists and surplus of 817 therapists by the year 2040, influenced by dentist working patterns, specialization, and privatization. Increasing the potential for specialist training and permitting emerging graduates’ to working part-time, while optimizing public sector primary care, and responding to the career expectations of emerging graduates, has the potential to absorb potential oversupply, and, thus, utilize the entire clinician dental workforce in Malaysia in the medium term. Conclusion: The findings of this model demonstrate the short-term requirement to expand the Malaysian dental workforce to meet dental needs of the population, highlighting that continued production at the current rate will result in oversupply, unless action is taken to maximize primary care, enhance specialization, and embrace flexible working to meet career expectations of graduates.